THE EFFECT OF STRATEGIC ORIENTATION, TRANSFORMATIVE INTERACTION CAPABILITY, TECHNOLOGY INFORMATION AND TASK IMPLEMENTATION QUALITY ON TEAMWORK PERFORMANCE - Tanzilal Azizi Rohmah; Ika Nurul Qamari; Meika Kurnia Puji RDA (Indonesian Journal of Multidisciplinary Science, 2022)
This study aims to examine empirical evidence about the relationship between strategic orientation, transformative interaction capability, information technology and task implementation quality on teamwork performance in high school in Pringsewu district, Lampung. This study uses a quantitative research approach to investigate the relationship between strategic orientation, transformative interaction capability, information technology and task implementation quality on teamwork performance. To achieve the research objectives, data were collected from stakeholders from several high schools in Pringsewu district, Lampung, Indonesia. Using structural equation modeling, and after a series of exploration and confirmation factors were analyzed, the authors tested an integrated model of the relationship between strategic orientation, transformative interaction capability, technology information and task implementation quality on teamwork performance. The results of this study indicate that strategic orientation has a positive and significant effect on teamwork performance. transformative interaction capability has a positive and significant effect on teamwork performance. task implementation quality has no significant effect on teamwork performance. and information technology have a positive and significant effect on teamwork performance